مدى شرعية زواج المسيار وحاجة المجتمع الماليزي إليه /c - Fhauziah Zakaria (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2008)
The issue of misyar marriage is a new issue that has recently been widely talked about in Malaysia. Not many actually understand its meaning, mechanism and Islamic ruling on it. This type of marriage is not covered by any law in Malaysia and is not officially regulated. This is because the Malaysian Shari'ah courts have no provisions on forms of marriage except those related to the normal form of matrimony. In light of this, the researcher has conducted a study on this issue to bring to light the abstruse aspects of this concept of marriage, highlighting the rulings related to it, the views of the scholars and its objectives in terms of their conformity to the general objectives of the shari'ah. The researcher also analyses the views given by respondents sampled from the Malaysian society and investigates the extent of the need for this marriage.The deductive method has been used to collect data on the opinions of contemporary scholars, from amongst those who allow it and those who oppose it. The analytical method is used to scrutinize those opinions and discuss the evidence they adduced. Interviews were also conducted with Malaysian scholars and officials working in the related field. Some of those interviewed include a mufti, a shari'ah court judge and some researchers in shari'ah sciences and family law in International Islamic University Malaysia.The study came to a conclusion that misyar marriage could be practised within a limited boundary and be treated as an exception rather than a rule for those who need it. The researcher recommends that this marriage be made permissible and the Malaysian government should give incentives and sufficient assurances for it to operate properly within certain provisions of the law. This is for the benefit of those who could not get married in the normal form so that they can fulfill their need to form a family. This way, the problem of spinsterhood can be solved as well as the problem of those who are divorced or widowed. It is incumbent upon the society to accept this type of marriage because there is nothing in it that goes against the general objectives and the spirit of the shari'ah.